Ciência no tribunal: as expertises mobilizadas no caso Belo Monte - Rodrigues, Luciana Rosa (2013)
My thesis treats about the scientific and technical knowledge used by the judge system and the federal public ministry in the Belo Monte case. It tries to explain how science proves are translated by the judge system and the federal public ministry, and also how they verify which are the principal experts mentioned. In this thesis I also define the arguments and actors that where legitimize in the Belo Monte case. It talks about how science merges with the judge system and how is treated and interpreted by people, that don t have the specific knowledge in science and technology in this field. It stars from this question: How judges discern from choosing between the technical documents produced by the people who claim, and the defendant documents, when this two are contradictory? Is there a way for this? After, all fifteen initial cases are specifically analyzed to verify which arguments and professionals are more relevant and repeated. Then, two sentences are analyzed to conclude which expertise did the judge system legitimated or not. This work is based on a ground study made by the author in Belem and Campinas, where I had access to some lawsuits of the case. I also interviewed key interlocutors that helped the federal public ministry with scientific studies. For making this,I Will use the Latour s concept of translation, the Harry Collins and Evans expertise concept, and also studies of Sheila Jasanoff about science in the United States courts. Speech analyze will also be addressed as a method of interview interpretation.